Unpacking drought impacts and adaptive strategies in Morocco – perspectives from small-scale farmers - Shrimpton, Elisabeth A.; Sarmah, Tanaya; Balta-Ozkan, Nazmiye; Malki, Sanaa; Jelloul, Ahmed; Ouikhalfan, Mohammed; Nilahyane, Abdelaziz; Kouisni, Lamfeddal; Huo, Da (Elsevier, 2025)
Droughts in North Africa are increasing in frequency and severity. The most vulnerable include small-scale farming communities and the associated small businesses with wide-ranging impacts and demands on local communities, food production, water allocation, and energy requirements. Our solution-orientated study supports the mitigation of impacts and the management of droughts in two case study areas within Morocco. A 2-day workshop was conducted to engage with local farmers in Settat and El Jadida to better understand the drought impacts and associated adaptive strategies. A Fuzzy Cognitive Mapping (FCM) approach was used to actively engage and interact with the farmers and to gain an understanding of the interconnections between drought, coping mechanisms, adaptation strategies, and issues to their livelihood and as seen through their experiences. The perspectives give new insights into where the policy interventions for the most impact in the system might be.
Corrigendum to ‘Unpacking drought impacts and adaptive strategies in Morocco – perspectives from small-scale farmers’ [Int. J. Disaster Risk Reduct. 128 (2025), 105732] https://doi.org/10.1016/j.ijdrr.2025.105754
Keywords: 4406 Human Geography; 44 Human Society; 13 Climate Action; 4404 Development studies; Agricultural drought; Drought indicators; Fuzzy cognitive mapping; Small-scale farmers